Sikap Ibu Hamil dengan Kepatuhan Imunisasi Tetanus Toxoid di Puskesmas Waisai Kabupaten Raja Ampat - Baktianita Ratna Etnis (Jurnal Ilmiah Kesehatan (JIKA), 2020)
Coverage of tetanus toxoid immunization in Waisai Health Center Raja Ampat Regency is still low and has not reached the national target, especially for pregnant women. The study aimed to determine the relationship between attitudes of pregnant women with adherence to tetanus toxoid immunization in the Waisai Health Center in Raja Ampat Regency. This type of research used quantitative methods with a cross sectional study design. The study was conducted at the Puskesmas Waisai Raja Ampat Regency in February-March 2019. The sample in this study used a total sampling of 49 subjekts. The instrument used was a questionnaire. Chi Square statistical test results showed a significant value of attitude p=0,001 (? <0,05), thus there was a relationship between the attitude of pregnant women with compliance with tetanus toxoid immunization in Waisai Health Center in Raja Ampat Regency. The conclusion of the study is there is a relationship between the attitude of pregnant women with tetanus toxoid immunization compliance in Waisai Health Center, Raja Ampat Regency.